Building Virtual Reality Hajj Journey Learning Media as a Simulation Tool for Teaching Hajj and Umrah Topics - Ramadhan, Mochammad Rizal; Mutiara Hasanah, Samudra; Khoirunnisa, Tsania; Medhi Sampurno, Tri Anggara; Faizin, Nur; Sultoni, Achmad; Nurdiyanto, Reno; bin Rekan, Abd. Aziz (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2025)
The need for more engaging Hajj and Umrah education highlights the limitations of conventional methods, such as lectures and printed manuals, which often lack experiential and spiritual depth. While Virtual Reality (VR) has become increasingly common in education, its use in religious ritual training, particularly for Hajj and Umrah, remains largely underexplored. This study aims to develop immersive learning media that allow users to practice Hajj and Umrah rituals interactively. The development of the VR-Hajj application followed the Research and Development (R&D) model by Lee and Owens, which includes five stages: analysis, design, development, implementation, and evaluation. The validation process involved experts who assessed the media’s content, usability, and instructional design. Data were analyzed using inter-rater agreement to determine consistency among expert evaluations, with results showing a high level of agreement. The Content Validity Index (CVI) was also used to assess overall validity, yielding a strong score of 0.83. Experts gave the VR-Hajj media an average rating of 91.54%, confirming its effectiveness and instructional relevance. These findings support VR-Hajj as a promising tool for improving Hajj and Umrah preparation through immersive Islamic learning. The study also proposes a future framework integrating VR and metaverse technologies to enhance accessibility and engagement. To expand its impact, further research should explore strategic partnerships with Islamic boarding schools (pesantren) to help deliver VR-based religious education more widely and inclusively